Skills Acquired in Business Education Programme on Business Studies Teachers’ Performance in the Secondary Schools in Ogun State, Nigeria - Okuneye, Oluwasina Samson (The Indonesian Institute of Science and Technology Research, 2024)
The Business Education programme is expected to provide students with the entrepreneurial skills needed to thrive in the teaching industry. The Business Studies teachers seem not to have acquired adequate skills to be gainfully employed. This study assesses the impacts of Business Education programme skills on the performances of business studies teachers in Ogun state. The evaluation model of Context, Input, Process and Product by Stufflebeam crystallized the study. Two research questions and one hypothesis were tested. A survey research design was employed for this study. The population of the study comprised all public secondary school business studies teachers in Ogun Central Senatorial district A sample of 30 schools and 50 teachers were randomly selected. Two research instruments Questionnaires and Appraisal Scale were used in data sourcing. Analysis of data involved Mean, Standard Deviation, and independent T-test. This study identified some skills teachers were taught like teaching skills, office skills and accounting skills among others. The findings of the study revealed that the business studies teachers’ performances in the schools remain unattainable due to inadequate skill acquisition. Some recommendations were made among which are that Colleges of Education should liaise with the employers of labour to receive feedback on teachers’ performances in the teaching industry and that more qualified business educators should be employed to meet up with minimum standards of the NCCE.